Dissatisfaction with cardiovascular health and primary health care services: Southern Mani, isolated area in Europe. A case study. - Mariolis, Anargiros; Mihas, Constantinos; Alevizos, Alevizos; Mariolis-Sapsakos, Theodoros; Sergentanis, Theodoros N; Kalogerakos, Nikolaos; Virvilis, Christos; Fourkas, Constantinos; Skandalakis, Panayiotis; Stefanadis, Christodoulos (Hellenic J Cardiol, 2008)
INTRODUCTION: Access to local providers of primary health care (PHC) services and their utilisation is a challenge faced by the authorities of developed as well as developing countries. The aim of our study was to assess and evaluate the level of satisfaction with the currently provided cardiovascular and PHC services in the southernmost region of continental Greece (and of the European Union), Southern Mani. METHODS: The sample (422 individuals, 375 of whom finally participated: 187 men and 188 women, response ratio: 88.86%), was selected between January-December 2006, using stratified randomisation by sex and age. Participants were asked to fill in a validated questionnaire containing socio-demographic data and items about the health needs/level of satisfaction with cardiovascular health and PHC services, as well as two indices for cardiovascular health: i) frequency of international normalised ratio (INR) measurement in case of atrial fibrillation, and ii) history of timely thrombolysis in case of acute myocardial infarction. RESULTS: The majority of the responders stated that their level of satisfaction with PHC services was "low" or "very low" (total: 52.80%), while the percentage of dissatisfaction with cardiovascular health services was 56.0%. In addition, most of the participants expressed a strong wish for improvement of PHC services (71.33%). The level of satisfaction with PHC services was higher than with cardiovascular health services (2.49 +/- 1.26 vs. 2.38 +/- 1.24; p < 0.001). Satisfaction scores for both cardiovascular health and PHC services were negatively associated with the distance from the nearest PHC Unit. Only 11.1% of patients (95% CI: 0.3%-48.2%) reported annual testing of prothrombin time more than once, while among those with a history of acute myocardial infarction, none reported timely thrombolysis (0%, one-sided 97.5% CI: 0%-41.0%). CONCLUSION: It is evident that a large portion of the Southern Mani population perceives the provided cardiovascular health and PHC services as problematic, while the distance from the nearest PHC unit seems to be one of the most important factors and predictors of dissatisfaction. The provision of efficient PHC services in isolated areas is a matter that should be re-evaluated.
Keywords: Cardiovascular Diseases; Female; Greece; Health Care Surveys; Health Services Accessibility; Humans; Male; Middle Aged; Patient Satisfaction; Primary Health Care; Quality of Health Care; Rural Health Services